Euro-Med And Intercultural Management - Issam Atala (European Scientific Journal, ESJ, 2016)
As technological inventions and innovations are bewildering the human mind, destroying barriers between peoples, cultures, time and space, globalization trends are sweeping civilizations, nations, nationalisms and other ethnic narrow circles. The winds of human revolutions overwhelm governments, leaders and citizens in pursuit of a better world, based on human freedoms and rights, economic well-being, peace and sustainable ecosystem. This positive cultural change is subjected to many obstacles and much dichotomy, whereby some do promote a negatively extreme pole of violence, terror and death. The objective of this research is to deeply explore the inner venues of both trends, embraced by a new breed of international mangers, leaders, and further determine their impact upon the birth of a world culture, primarily adopted by international businesses. The proposed methodology of research relies, primarily on data gathering from many thinkers and organizations aiming at laying a possible foundation for promoting intercultural management between Europe and the Middle Eastern countries.